Iran’s Responsibility for the MV Mercer Street Attack under International Law - Gunawan, Yordan; Anggoro Wati, Elvita; Corral, Eva Ferrer (Brawijaya Law Journal, 2023)
The use of new technological developments in warfare, such as unmanned aerial vehicles (UAVs or drones), has become a threat to international law due to the infliction of unnecessary suffering and injuries. In late July 2021, the MV Mercer Street, managed by Israeli-owned Zodiac Maritime, was attacked by three one-way drones while transiting on the high seas of Oman. In such a situation, international peace and security are threatened. Based on an investigation by U.S. Central Command (CENTCOM) and all evidence available, the Group of Seven (G7) foreign ministers pointed to Iran as the state responsible for the attack. This conclusion was based on the fact that the vertical fin was identical to those seen on an Iranian-designed and manufactured one-way attack “kamikaze” UAV series. The investigations stated that Iran was actively involved. However, Iran rejected any responsibility for the attack. What is Iran’s responsibility for the MV Mercer Street incident from an international legal perspective? The research aims to determine the international legal perspective on the use of armed force. The study is normative legal research, in which the data are collected through a statutory approach and case approach. The result of the study shows Iran's responsibility is necessary for using armed drones as an advantage of new technologies that do not consider the principles of necessity and proportionality in armed conflict. Furthermore, the research provides an understanding of Iran's responsibility under international law regarding using armed forces against other states.